Cilioretinal arteries and collateral vessels after occlusion of central retinal artery - Petrović, Nenad; Šarenac, Tatjana; Todorović, Miloš; Srećković, Sunčica; Petrović Janićijević, Mirjana; Janićijević, Katarina (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Central retinal artery occlusion (CRAO) is a disease of the eye where the flow of blood through the central retinal artery is blocked. It causes sudden, painless, unilateral and usually severe vision loss. The aim of our study was to examine significance of cilioretinal artery on collateral and neovasculatization development after occlusion of the central retinal artery. Мethods. This study retrospectively reviewed all fluorescein angiography (FA) cases with confirmed CRAO and presenting, one or more, cilioretinal arteries on initial examination. The study included patients referred to the Clinic of Ophthalmology, Clinical Center Kragujevac for the examination in the period from January 2010 to January 2015. Ten eyes of 10 patients with confirmed CRAO and existing cilioretinal artery on initial examination were found and analyzed in this study. Results. This study included 10 (6 males and 4 females) patients from 50 to 76 years old (mean 66.3 ± 10.078 years). Visual acuity on initial examination presented on the decimal scale was from 0.01 to 0.2 (mean 0.087 ± 0.066). Intraocular pressure measured by applanation tonometry was in the range from 14 to 20 mmHg (mean 16.7 ± 2.540 mmHg). Cilioretinal artery was revealed on the first FA examination of all eyes. On control FA, in three eyes de novo collaterals were discovered. In the first eye, collaterals were discovered after two months, in the second eye after four months, and in the third eye after seven months of the performing the initial angiogram. Visual acuity was checked after one year. It was from light perception to 0.03 (mean 0.016 ± 0.009). Conclusion. The presence of cilioretinal arteries with preexisting or de novo developed collaterals was not enough to preserve visual acuity and prevent neovascularisation over a longer period after CRAO.